Principles of curricular design from complexity: the case of the National Technical University (Revista Electrónica Calidad en la Educación Superior, 2021)
This essay carries out a proposal of curricular principles from complexity to the case of the National Technical University (UTN), Costa Rica's only public university with an Educational Model based on complexity. For this purpose, a theoretical curriculum approach is carried out and the contributions of complexity are integrated from the cross-cutting axes and principles of flexibility, integration, eclecticism and quality, incorporating operational elements for its implementation in curriculum designs. The essay allows to conclude the existence of guidelines and operational principles for curriculum design from the premises of complexity and allows to establish research scenarios for other substantive elements of the design, implementation, and evaluation of the university curriculum.
Keywords: Curriculum; complexity; curriculum design; curricula; higher education